Stress analysis on front car bumper - Jamail, Jamal (2009)
The project focuses on the stress analysis of a car frontal protection system (bumper) simulations. To achieve that, we go to basic concepts of improving the safety on the car by do analysis the car bumper. It is important to know their mechanical properties, how their failure mechanism during the impact. This analysis was carrying out by using commercial Finite Elements software (ALGOR) to evaluate the behavior of bumper system. Another additional innovative for improving crashworthiness is the use of material to produces the part to absorb energy during the process of a crash. Research concentrates on polymer composite material. It is considering their function, geometry, and other parameters that influence the compatibility of the bumper. In future research, this bumper will face the static test and analyses do on their load distributions by applying the variation of load and locations. Result will be compare for the centre and side load. How the load applied effect the stress distrubution. After that a related study was carried out to know bumper properties during the impact.